Levels of soluble ICAM-1 in premature and full-term neonates with infection. Issue 2 (2002) - Apostolou, Melita; Dimitriou, Helen; Kaleyias, Joseph; Perdikogianni, Chrissoula; Stiakaki, Eftichia; Costalos, Christos; Kalmanti, Maria
Abstract : Background : Infection in the neonatal period is an extremely serious condition and diagnosis is difficult. C-reactive protein (CRP) is widely used as a marker of infection; however, its usefulness is limited in the early phase. The role of soluble intracellular adhesion molecule-1 (sICAM-1), an adhesion molecule, has been examined in recent studies as an early marker of neonatal infection with controversial results. Aim : Assessment of sICAM-1 concentrations and correlation with CRP, which is the currently used marker of infection, in order to use sICAM as an early diagnostic tool in neonates suspected for infection Methods : Blood samples and blood cultures were obtained from two groups of pre-term and full-term neonates with clinical suspicion of infection prior to the initiation of antibiotics. The sICAM-1 and CRP values were compared with the corresponding non-infected ones ( n = 10 each). Results : The sICAM-1 levels were found increased in the group of both premature and term neonates with infection compared with the corresponding healthy ones (p < 0.0001 ). Prematurity combined with infection resulted in excessive increase of the levels of sICAM-1 in comparison with full-term infected newborns (p < 0.001 ). CRP values were normal in all samples except one in both full-term and premature infected neonates on day 1 of clinically suspected infection. Serial detection of CRP values on days 2 and 4 of infection revealed a pattern according to which CRP values in premature neonates continued rising, while in the group of full terms these values, after rising on the second day, lowered on day 4. Conclusions : Increased sICAM-1 levels can be detected early in both full-term and premature neonates with sepsis while CRP levels are within normal range at the sametime. Assessment of sICAM-1 concentrationsmay be used as a diagnostic tool in neonates suspected for infection, resulting in earlier initiation of antibiotic therapy and therefore improving their outcome.